Amelioration of ocean acidification and warming effects through physiological buffering of a macroalgae. Issue 15 (19th July 2020) - Doo, Steve S.; Leplastrier, Aero; Graba‐Landry, Alexia; Harianto, Januar; Coleman, Ross A.; Byrne, Maria
Abstract: Concurrent anthropogenic global climate change and ocean acidification are expected to have a negative impact on calcifying marine organisms. While knowledge of biological responses of organisms to oceanic stress has emerged from single‐species experiments, these do not capture ecologically relevant scenarios where the potential for multi‐organism physiological interactions is assessed. Marine algae provide an interesting case study, as their photosynthetic activity elevates pH in the surrounding microenvironment, potentially buffering more acidic conditions for associated epiphytes. We present findings that indicate increased tolerance of an important epiphytic foraminifera, Marginopora vertebralis, to the effects of increased temperature (±3°C) and p CO2 ( 1, 000 µatm) when associated with its common algal host, Laurencia intricata . Specimens of M. vertebralis were incubated for 15 days in flow‐through aquaria simulating current and end‐of‐century temperature and pH conditions. Physiological measures of growth (change in wet weight), calcification (measured change in total alkalinity in closed bottles), photochemical efficiency ( Fv/Fm ), total chlorophyll, photosynthesis (oxygen flux), and respiration were determined. When incubated in isolation, M. vertebralis exhibited reduced growth in end‐of‐century projections of ocean acidification conditions, while calcification rates were lowest in the high‐temperature, low‐pH treatment. Interestingly, association with L. intricata ameliorated these stress effects with the growth and calcification rates of M. vertebralis being similar to those observed in ambient conditions. Total chlorophyll levels in M. vertebralis decreased when in association with L. intricata, while maximum photochemical efficiency increased in ambient conditions. Net production estimates remained similar between M. vertebralis in isolation and in association with L. intricata, although both production and respiration rates of M. vertebralis were significantly higher when associated with L. intricata . These results indicate that the association with L. intricata increases the resilience of M. vertebralis to climate change stress, providing one of the first examples of physiological buffering by a marine alga that can ameliorate the negative effects of changing ocean conditions. Abstract : We present findings that indicate increased tolerance of an important epiphytic foraminifera, Marginopora vertebralis, to the antagonistic effects of increased temperature and p CO2, when associated with its common algal host, Laurencia intricata . When incubated in isolation, M. vertebralis exhibited reduced growth in end‐of‐century projections of ocean acidification conditions, while calcification rates were lowest in the high‐temperature, low‐pH treatment. Interestingly, association with L. intricata ameliorated these stress effects with the growth and calcification rates of M. vertebralis being similar to those observed in ambient conditions.